1996
DOI: 10.1016/0020-7292(96)02684-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic fetal and placental tissue characterization and lung maturity

Abstract: The placental and fetal lung tissue of preeclamptic patients tended to have higher coefficients of variation throughout pregnancy. These results were significantly higher when associated with low-birth-weight babies. There were no significant differences in fetal liver tissue between normotensive and preeclamptic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Thus, intrauterine evaluation of foetal lung is clinically challenging, due to invasiveness and questionable efficacy of the available tests (Prakash et al, 2002;Varner et al, 2013). Development of accurate and non-invasive techniques, such as elastography, can provide an earlier and more precise diagnosis of lung abnormalities (Kim et al, 2013;Podobnik, Brayer, Ciglar, Duić, & Podgajski, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intrauterine evaluation of foetal lung is clinically challenging, due to invasiveness and questionable efficacy of the available tests (Prakash et al, 2002;Varner et al, 2013). Development of accurate and non-invasive techniques, such as elastography, can provide an earlier and more precise diagnosis of lung abnormalities (Kim et al, 2013;Podobnik, Brayer, Ciglar, Duić, & Podgajski, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…8). The coefficient of variation corresponds to the Mean/Standard Deviation (MEAN/STD) (Podobnik et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are a variety of feature extraction algorithms applicable to ultrasound images, but a few study have been reported on the placental tissue development. In a previous study (Podobnik et al, 1996), the ultrasonic placental tissue development is characterized by a coefficient of variation according to the week of gestation. No relation exists between the week of gestation and the development of the grade.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound is already well stablished as a viable and non-invasive way to evaluate foetuses and its tissues, and a promisor alternative for the pulmonary maturity estimation. In humans, Podobnik, Brayer, Ciglar, Duić, and Podgajski (1996) analyzed echotextural attributes of the placenta, foetal liver and lung correlating the lung values with foetal maturity. Quantitative analysis of ultrasonography images has been used to establish normal canine hepatic echogenicity (Ivancic & Mai, 2008), and normal feline renal echogenicity (Drost, Henry, Meinkoth, Woods, & Lehenbauer, 2000).…”
Section: Contentsmentioning
confidence: 99%